If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35x + 12 = 4x + 3 Reorder the terms: 12 + 35x = 4x + 3 Reorder the terms: 12 + 35x = 3 + 4x Solving 12 + 35x = 3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + 35x + -4x = 3 + 4x + -4x Combine like terms: 35x + -4x = 31x 12 + 31x = 3 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + 31x = 3 + 0 12 + 31x = 3 Add '-12' to each side of the equation. 12 + -12 + 31x = 3 + -12 Combine like terms: 12 + -12 = 0 0 + 31x = 3 + -12 31x = 3 + -12 Combine like terms: 3 + -12 = -9 31x = -9 Divide each side by '31'. x = -0.2903225806 Simplifying x = -0.2903225806
| f(x)=2x(x+7)2x^2+14 | | 30=(5/9)(F-32) | | 30(9/5) | | x=(3)(3)(3) | | (6x+7)(2x+1)= | | 5n^2+13n-28=0 | | -4.9t^2+10t+2=0 | | 8-9p=1 | | 15a^2-22a-5=0 | | (3a+2)(a-2)= | | (-3)-(-10)= | | ((-7)-3)((-3)-(10))= | | x/5-x/10=3 | | 2x^4-6x^3+x^2+3=0 | | 13(2-x)=7(x+8) | | 5x+3x^2=25 | | c/a-p/a=1 | | f(x)=tan*3*x | | 6(x-3)-5=21x-4-10x | | 2x+x=59 | | 35+x+2x=42+9x | | 50-8x-3=15 | | 50-8x-3=16 | | 50-8x-3=18 | | 50-8x-4=18 | | 50-8x-5=18 | | 50-8x-6=18 | | 50-8x-12=18 | | 50-8x-11=18 | | 50-8x-13=18 | | 50-8x-14=18 | | 50-8x-14=15 |